Qualidade de vida, capacidade funcional e atividade física após o câncer mamário - Fontes, Karina Prado [UNIFESP] (2016)
Introduction: Surgical treatment of breast cancer can cause functional limitations, harming the daily activities of the patients. Objective: To assess quality of life, functional capacity and level of physical activity in patients who had undergone different types of surgical treatment of breast cancer. Methods: 180 women between 30 and 60 years of age were selected and allocated into four groups: Control (without breast cancer, n=45), Conservative Surgery (n=45), Mastectomy (n=45) and Breast Reconstruction (n=45). In order to assess quality of life, functional capacity and physical activity, the Brazilian versions of validated instruments were self-applied: the Medical Outcomes Study 36-item Short-Form Health Survey (SF-36), the Stanford Health Assessment Questionnaire (HAQ-20) and the International Physical Activity (IPAQ), respectively. Results: Groups were homogeneous in regard to age (overall average 48.5 years, p=0.5361) and body mass index (overall average 24,6kg/m2, p=0.5361). Mastectomy group significantly differedfrom Control group in the SF-36 domains "functional capacity" (p=0.004), ?physical aspects" (p<0.001), ?health perception? (p=0.036) and "emotional aspects" (p=0.001). Significant difference was observed between the Conservative and the Mastectomy groups regarding ?functional capacity? (p=0.022), ?physical aspects? (p=0.008) and ?health perception? (p=0.008). Regarding HAQ-20 scores, there was a statistically significant difference between the Control and the Mastectomy groups (p=0.006). In IPAQ there was a statistically significant difference between Reconstruction and Mastectomy groups (p=0.049) Conclusion: Patients who underwent breast reconstruction have a higher level of physical activity and quality of life, when compared to patients who underwent mastectomy alone or conservative treatment for breast cancer.